Evaluation of Type 2 Diabetes Risk in Individuals With or Without Metabolically Healthy Obesity - Miguel García Samuelsson; Pedro Juan Tárraga López; Ángel Arturo López-González; Carla Busquets-Cortés; Joan Obrador de Hevia; José Ignacio Ramírez-Manent (Biology)
Background: The concept of metabolically healthy obesity (MHO) has emerged as a controversial yet clinically relevant phenotype, challenging the traditional view that all obese individuals are uniformly at high metabolic risk. However, the long-term health implications of MHO, particularly its association with type 2 diabetes mellitus (T2DM), remain poorly defined. Objective: To assess the risk of T2DM in individuals with MHO compared to those with metabolically non-healthy obesity (MNHO), using multiple validated diabetes risk scales across a large population-based cohort. Methods: This cross-sectional study analyzed data from over 68,884 adults stratified by sex and BMI-defined obesity status. Metabolic health was categorized using three progressively inclusive definitions based on the number of metabolic syndrome components. Diabetes risk was estimated using Finrisk, Canrisk, TRAQ-D, Thai, Oman, and QD-score tools. Multinomial logistic regression assessed associations between MHO/MNHO phenotypes and high-risk diabetes scores, adjusting for demographic, socioeconomic, and lifestyle variables. Results: Across all definitions and scales, MNHO individuals exhibited significantly higher mean diabetes risk scores and greater prevalence of high-risk categories compared to MHO participants (p < 0.001). Nevertheless, MHO individuals consistently showed elevated diabetes risk relative to non-obese, metabolically healthy controls. Physical inactivity, low educational level, lower socioeconomic status, smoking, and absence of a Mediterranean diet were independently associated with higher diabetes risk. MNHO phenotype was a strong and consistent predictor of high-risk classification across all models. Conclusions: While MHO individuals present a comparatively lower risk of T2DM than their MNHO counterparts, their risk remains substantially higher than that of non-obese individuals. These findings highlight the need to refine risk stratification approaches beyond BMI alone, and to consider metabolic health status in guiding prevention strategies for T2DM.